A hybrid DIC–EFG method for strain field characterization and stress intensity factor evaluation of a fatigue crack. (15th March 2020) - Zhu, Zhihui; Luo, Sihui; Feng, Qianshuo; Chen, Yuanchang; Wang, Fan; Jiang, Lizhong
Highlights: Hybrid DIC-EFG method is used to obtain the accurate full-field strain and SIF. Tests and sensitivity analysis validated the accuracy and stability of the method. The method of establishing meshless model based on DIC speckle image is simple. The proposed method is able to implement without knowing the load and constraints. Abstract: A Hybrid DIC–EFG Method combining Digital Image Correlation (DIC) and Element-free Galerkin (EFG) method is proposed to characterize the strain field and study the fracture performance of a crack by evaluating the stress intensity factor (SIF). The full-field displacement data is measured by DIC. The meshless calculation model is developed by using the speckle image coordinate. Then the displacement data is imported into the model and strain is calculated by the EFG method. The SIF is obtained based on the J -integral method. A static tensile test with a quasi-static cyclic load is conducted on a Compact Tensile specimen (CT specimen) to experimentally validate the accuracy and stability of proposed method. The proposed method can effectively predict the strain at the crack tip, which is a great challenge for the DIC measurement. Compared with the reference ASTM standard, the proposed method can obtain the SIF accurately without knowing the geometry, load and boundary condition of the structure.